The Skin Interface - Meeting Point of Physiology and Clothing Science (Journal of Fiber Bioengineering and Informatics, 2008)
This paper describes the relevance of knowledge of processes that happen at the skin forsports clothing design. It looks at skin temperature distribution while cooling, relevant e.g. to outdoorwinter sports and mountaineering, at sweat distribution over the body while running, relevant e.g. toclothing designed for running in general and more particularly for exercise in warm and hot climates,and finally it looks into regional skin sensitivity, relevant for all fields of sports clothing design. Asthese areas interact heavily, the sports clothing designer needs to be aware of their influences and theirinteractions in order to optimise the clothing for the specific type of sport at hand.